2019
DOI: 10.3390/app9122484
|View full text |Cite
|
Sign up to set email alerts
|

Full-scale Studies of Improving Energy Performance by Renovating Historic Swedish Timber Buildings with Hemp-lime

Abstract: With an increased focus on reducing greenhouse gas emissions, energy saving is of great importance in all sectors of society. EU directives set targets for member states to reduce energy use in buildings. Energy saving in historic buildings requires special measures, balancing energy-saving renovations against the preservation of heritage values. Traditional constructions are open to vapor diffusion and generally work differently from modern constructions. Modern materials in traditional constructions sometime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…By adding hemp to the lime render and slightly increasing the thickness of the render, a significant improvement in the energy efficiency of the buildings was achieved. The proposed solutions not only preserve the historic form of the buildings, but are almost entirely in line with traditional construction techniques [16].…”
Section: Cultural Heritage and Sustainable Developmentmentioning
confidence: 83%
“…By adding hemp to the lime render and slightly increasing the thickness of the render, a significant improvement in the energy efficiency of the buildings was achieved. The proposed solutions not only preserve the historic form of the buildings, but are almost entirely in line with traditional construction techniques [16].…”
Section: Cultural Heritage and Sustainable Developmentmentioning
confidence: 83%
“…Thanks to their thermal performance, the hemp composites have been positively considered for the building refurbishment or restoration [60]. Some papers discuss the energetic performance of historic buildings after the application of hemp-lime compared with gypsum lime [61]. For instance, Agliata et al [62], using a case study "Palazzo Jadicicco", found that the overall energy performance of the building increased by around 20% with a one-level improvement of the building energy class, from E to D. Besides, if it is a good result, it should underline that the decrease in thermal transmittance was not sufficient to fulfill the regulatory requirements, in Italy.…”
Section: State-of-artmentioning
confidence: 99%
“…Traditional houses have a distinctive shape with features that depend on the climate, culture, environment, and the location of the country in which they are built. Strandberg-de Bruijn, Donarelli, and Balksten have conducted research for the preservation and development of traditional architecture in the region, through the case of historic Swedish timber buildings, the most historic single-family houses in Sweden [11]. Their concept is quite impressive, and the main issue suggests that it will be necessary to improve the architectural performance of historical buildings with materials suitable for the architectural framework, while preserving its characteristic elements.…”
Section: Literature Reviewmentioning
confidence: 99%